2018
DOI: 10.1093/jas/sky485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a porcine reproductive and respiratory syndrome outbreak on genetic parameters and reaction norms for reproductive performance in pigs1

Abstract: The objective of this study was to estimate genetic parameters of antibody response and reproductive traits after exposure to porcine reproductive and respiratory syndrome virus. Blood samples were taken approximately 60 d after the outbreak. Antibody levels were quantified as the sample-to-positive ratio (S/P ratio) using a fluorescent microsphere assay. Reproductive traits included total number born (TNB), number born alive (NBA), number stillborn (NSB), number mummified (NBM), and number born dead (NBD). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(35 citation statements)
references
References 34 publications
(87 reference statements)
4
28
3
Order By: Relevance
“…Previous studies have shown that antibody response to PRRS virus following PRRS infection is associated with reproductive outcomes during natural PRRS infection 7,8 . In addition, a relationship between the microbiota and immune response has been observed 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that antibody response to PRRS virus following PRRS infection is associated with reproductive outcomes during natural PRRS infection 7,8 . In addition, a relationship between the microbiota and immune response has been observed 5 .…”
Section: Discussionmentioning
confidence: 99%
“…These authors measured S/P ratio at about 46 days after the PRRS outbreak using the same ELISA test utilized in our study. Also using purebred pregnant sows under a PRRS outbreak, Putz et al (2019) reported a much lower h 2 estimate, of 0.17 ± 0.05 during the PRRS outbreak. In their study, antibody response to PRRSV was measured at about 60 days after the PRRS outbreak.…”
Section: Heritabilitiesmentioning
confidence: 91%
“…In their study, antibody response to PRRSV was measured at about 60 days after the PRRS outbreak. There were three main differences between Serão et al (2014) and Putz et al (2019) that could be associated with different estimates of h 2 observed. First, the time of sample collection in Putz et al (2019) was of about 2 weeks after the PRRS outbreak than in Serão et al (2014), which could indicate a different immunological response of the animals (further discussion below).…”
Section: Heritabilitiesmentioning
confidence: 97%
See 2 more Smart Citations